ANALYSIS OF HEALTH SERVICES QUALITY USING SERVQUAL METHOD IN CORRECTIONAL INSTITUTIONS CLASS IIA KOTABUMI - Kurnia, Aldiko Tisa Dwi; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research is to analyze whether there are problematic attributes in the health services provided by the Kotabumi Class IIA Penitentiary, which are the needs of its inmates, using the ServQual and Importance Performance Analysis methods. This research was then carried out using quantitative methods. Data collection in this research was carried out by distributing questionnaires to respondents, where the respondents in question were samples taken from sick prisoners in December 2023 in the Class IIA Kotabumi Correctional Institution. In the research, the researchers used random sampling techniques. The population used was 142 respondents. Sampling was carried out using the Krejcie Morgan table. The findings show that the services provided by the Kotabumi Class IIA Penitentiary have not fully met the expectations of the prisoners in the prison. Keywords: Quantitative; Gap; Importance Performance Analysis; ServQual